Fusobacterium nucleatum Osteomyelitis of the Femur in a Patient with Hereditary Hemorrhagic Telangiectasia: A Case Report. Issue 1 (January 2016) - Foran, Ian; Kinney, Matthew C.; Botte, Michael J.; Covey, Dana C.
Abstract : Case: Hereditary hemorrhagic telangiectasia (HHT), also known as Osler-Weber-Rendu syndrome, is an often overlooked cause of orthopaedic-related infections despite a well-accepted association in the literature. We present the case of a forty-seven-year-old man with HHT who developed femoral osteomyelitis and a subsequent pathologic femoral fracture from a rare bacterial species associated with HHT. Conclusion: Patients with HHT and extremity pain should be carefully evaluated for orthopaedic infections. If an orthopaedic infection is suspected, fastidious organisms should be considered as a possible etiologic agent. PCR (polymerase chain reaction) is helpful when organisms cannot be isolated from traditional culture media.